Gambaran Tugas Kesehatan Keluarga Dalam Perawatan Tuberkulosis Paru Di Rumah Di Wilayah Kerja Puskesmas Citeras Kabupaten Garut - Riyana, Asep (Jurnal Kesehatan, 2024)
In 2013, WHO estimates that each year there are 13,000 new cases of tuberculosis. West Java in the number of tuberculosis at the national level which occupies the number 1 (± 18%). An increase in the numbers of tuberculosis patients in Garut regency between 2013 and 2014. The study was conducted aiming to see the picture in the Family Health Task Tuberculosis Care at Home. Tuberculosis is an infectious disease caused by mycobacterium tuberculosis. Duties of family health in the prevention of infectious diseases is necessary because the family is the unit of health care at the forefront of improving the health of communities. The study design used is descriptive quantitative total respondents 30 people. The variables studied were family health task in identifying health problems, making decisions, and giving health care. Results of this study, the frequency distribution of pulmonary tuberculosis patient families who are unable to recognize the health problems of pulmonary tuberculosis 21 respondents (70%), family pulmonary tuberculosis patients who are unable to make decisions 22 respondents (73.3%), family pulmonary tuberculosis patients who are unable to provide care at home 27 respondents (90%). Health education using the media and the language that is easily understood by family, making it easier for families to absorb the information given by health professi\onals and family can minimize the transmission of diseases of pulmonary tuberculosis.